Effective regulatory frameworks for constructive journalism: a study of China’s media systems - Gopolang Ditlhokwa; Sarah Marjorey Kisakye; John Demuyakor; Sampson Hodor (International Journal of Communication and Society, 2023)
Journalism practice in China is unique and different from the rest of the other countries in the world. Many scholars have attributed this to the effective regulatory systems and the structure of the media system thus the six forces controlling media space in China. This study adopted a qualitative condensed thematic analysis technique through in-depth interviews to examine how the regulatory framework in China affects the media ecosystem and constructive journalism practice. Through the snowball technique of sampling, the researchers collected data from fifteen (N=15) senior media professionals working within private and state-owned news outlets in China, to find answers to the nature of the media system in China and how this system has influenced and shaped constructive journalism practice during the COVID-19 pandemic between November and December 2021. One of the key findings of this study indicates that the robust media regulatory system practice in China has resulted in effective interactions among stakeholders, media houses, and journalists within the Chinese media system, which has significantly contributed to attaining effective constructive journalism practices. Again, our findings suggest that the effectiveness and constant interactions of the six forces of the Chinese media system have also helped enforce professionalism, dedication to duty, and patriotism among journalists and different media outlets in China. Finally, our study reveals that the Chinese Media giants such as China Global Television Network (CGTN), China Central Television (CCTV), and China Radio International (CRI) which serve millions of global audiences are very factual in their reportage. To avoid fake news in their reportage, CGTN and China Radio International, for instance, have designed specialized fact-checking programs for their news stories before airing them for public consumption.